Plasma magnetic time-varying nonlinear robust control system for the Globus-M/M2 tokamak. (July 2020) - Mitrishkin, Yuri V.; Prokhorov, Artem A.; Korenev, Pavel S.; Patrov, Mikhail I.
Abstract: This paper is devoted to the development of the magnetic plasma control system for the Globus-M/M2 spherical tokamak (ST) when minor disruptions occur. The novelty of the research is the design of robust cascade multivariable control systems for time-varying plasma models in the presence of nonlinear thyristor current inverters as actuators for plasma position control. A new architecture of coordinated control of plasma position and shape is proposed. Quantitative Feedback Theory is used for the synthesis of robust Single-Input Single-Output (SISO) controllers for plasma position and PF-currents. Multiple-Input Multiple-Output (MIMO) H ∞ control is applied to control the plasma shape. The simulation results of the gaps-based MIMO plasma shape control system with the plasma equilibrium reconstruction code in the feedback are shown. The robust stability of the control system is estimated.